(Heat Pump Drying (HPD) ; Mechanism, technical Analysis, Classification and Its Application) - Rizal Alamsyah (Warta Industri Hasil Pertanian, 2005)
Heat pump drying (HPD) is one of innovative drying methods due to many advantages in drying for agricultural,food,and timber product.HPD is a drying can employ significant reduction of the energy consumption by energy recovery from condensation humudity.Comparing to orther drying methods such as fluidized,spouted, vaccum drying,HPD was leading in high water removal (kg H2O/kw/hour), wide operating drying temperature scale,wide operating humidity,better quality products,and low operational cost.So far HPD still has some limitation in its application such as the use of CFCs (Cloro fluoro carbon)as refrigerant that is not environmental friendlier,needs regular maintenance for all components of drying system including refrigerant charging, the possilibities for leak of refrigerant, and increase of operational cost.In drying food product,application of HPD was succesful especially in resulting uniform moisture contant,better tensile strength.Timber drying was also enhanced by HPD and the result show that the dried timber has better quality in terms of reduction brown tain in radiana pine,collapse,case hardening,and warpage.The latest tecnology of HPD was hybrid HPD covering fluidized bed HPD,infra red HPD, radio freqiency HPD, solar energy HPD,and multiple chambers of HPD.